Exosome-Based Delivery of Natural Products in Cancer Therapy - Song, Hang; Liu, Bin; Dong, Bin; Xu, Jing; Zhou, Hui; Na, Sha; Liu, Yanyan; Pan, Yunxia; Chen, Fengyuan; Li, Lu; Wang, Jinghui (Frontiers in Cell and Developmental Biology, 2021)
A rapidly growing topic of research evidence has begun to shed light on the wide of potential applications on exosome which modulate intercellular communications. As a donor cells release vesicles, exosome could play as a regulator of cellular behavior for uptaken cells, as well as a delivery carrier of drugs for targeted cells. Natural product is a kind of invaluable drug sources and it is using widely as therapeutic agents in cancer. This review summarizes the most recent developments in exosome as natural Products delivery carriers in cancer therapy from following perspectives: composition and biogenesis of exosomes, and its functions in cancer. It was focus about advantages and applications of exosomes as drug delivery in cancer therapy. This review also summarizes the isolation and applications of exosomes as delivery carriers of natural products in cancer therapy. The recent grogress and challenges, focused on five representative anti-cancer natural products (including paclitaxel, curcumin, doxorubicin, celastrol and β-Elemene) used by exosomes as drug delivery vehicles were discussed in this review. Based on the elaborately discussion with current knowledge about exosomes as delivery vehicles for drugs and natural compounds to the targeted site, this review delineates landscope of the recent research, challenges, trends and prospects in exosomes as delivery vehicles for drugs and natural compounds for cancer treatment.